Etnomatematika Geometri Piramida pada Kuliner Tradisional: Kue Lepek, Binti, Lupis, dan Lepat Singkong - Masayu Iddha Zahrani; Andre Andre; Rani Widya; Adi Asmara (Civiliza Publishing, Indonesia., 2026)
Ethnomathematics is a field of study that connects mathematical concepts with the cultural activities of a community. Traditional cuisine is one form of culture that contains many mathematical concepts. This study aims to identify the mathematical concepts found in three traditional foods, namely Lepek Binti cake, Lupis cake, and Lepat Singkong. The study used a descriptive qualitative method with a literature-based approach combined with ethnomathematical analysis of the making process, form, and presentation of the three foods. The results show that all three traditional foods contain various mathematical concepts, such as plane and solid geometry, measurement, comparison, ratio, algorithm, pattern, symmetry, and estimation. In addition, the wrapping form of several types of food shows a representation of solid shapes resembling a pyramid, which can be used as a contextual learning medium for geometry. These findings indicate that traditional cuisine can be utilized as a contextual source of mathematics learning while also serving as an effort to preserve local culture